Buildings Energy-Efficient Renovation Investment - Sivitska, Svitlana; Vartsaba, Vira; Filonych, Olena (International Journal of Engineering and Technology, 2018)
The scientific approach to the definition of strategic investment priorities in the complex renovation of areas affected by natural and technology-related emergencies, the introduction of energy-efficient technologies and alternative energy, which involves the construction of strategic priorities selection matrix with the investment processes coordination in the regional and alternative energy sectors is proposed. Its carrying out allows to improve the investment management process in multivariance terms of investment process implementation options. Influence on certain elements of the territories renovation organization, which will facilitate the additional resources investment involvement for the building structures renovation, is determined.The economic effect of the research and development introduction is to reduce the energy and material intensity of the reconstruction complex of works due to the most efficient materials use, as well as the reduction of construction time, labor costs and energy consumption during construction.Â Â
Keywords: alternative energy; area renewal; energy efficiency; renovation of buildings; state construction policy; strategic priorities.